NILAI-NILAI PENDIDIKAN ISLAM DALAM TRADISI SEDEKAH DESA DI DESA JAMBUWER KECAMATAN KROMENGAN KABUPATEN MALANG - Musadat, Irfan; Jefri, Jefri (JIPI (Jurnal Ilmiah Pendidikan Islam), 2022)
This study aims to describe the values of Islamic education in the village alms tradition in Jambuwer Village, Kromengan District, Malang Regency. This study uses a qualitative method, the informants of this research are the village head, village secretary, village elders and community leaders in Jambuwer village with a total of 6 people. This study uses data collection techniques through interviews, observation, and documentation. The data analysis technique used is data reduction, data compilation and categorization. The results of this study are as follows: (1) The village alms tradition means the gratitude of humans or the local community to Allah SWT, this is what underlies the village alms tradition. Village alms are a tradition that has been passed down from generation to generation by the people of Jambuwer village. (2) The values of Islamic education contained in the village alms tradition are the first values of aqidah, which is about faith. In the village alms there is prayer and tahlil as the beginning of the village alms ceremony, it shows that even though holding any event one must remember and believe in Allah SWT on the basis of faith. The two values of gratitude, such as the meaning of the village alms tradition itself, namely gratitude, gratitude is something that reflects the good teachings of Islam. Third, there is the value of worship because in the implementation of the village alms tradition, the holy verses of the Qur'an are chanted. The fourth is the value of unity where the community realizes that humans cannot live alone without the help of others, and with unity, village alms activities can run smoothly. The five values of deliberation are that before the village alms activity is held, all community members hold a deliberation for the implementation of village alms activities so that they run smoothly. The six values of gotong royong where the community helps each other start from the preparation of equipment, preparing dishes to the completion of the village alms event. Keywords: Islamic Education Value, Tradition, Village Alms